Perlindungan Hukum Masyarakat Adat atas Tanah Ulayat Pasca Berakhirnya Hak Guna Usaha dalam Perspektif Hukum Agraria Indonesia - Satriani Satriani (CV. Rumoh Aceh Publishing, 2026)
indigenous law communities (masyarakat hukum adat) in Indonesia. Although the existence of these communities is constitutionally recognised under Article 18B(2) and Article 28I(3) of the 1945 Constitution and Article 3 of the Basic Agrarian Law (Law No. 5 of 1960), such recognition remains conditional and must accord with national development interests. Problems frequently arise when the State grants a Right of Cultivation (Hak Guna Usaha/HGU) over land that indigenous communities regard as their ulayat land, and further disputes emerge once the HGU expires, as the land's status becomes contested between the State and the indigenous claimants. This normative legal research examines the legal status of ulayat land after the expiry of HGU and the forms of legal protection owed to indigenous communities, using statutory, conceptual, and case approaches, illustrated by the ongoing dispute between the Ndonganeno–Weri Bone indigenous community and the local government over former HGU land of PT Kapas Indah Indonesia in Konawe Selatan. The study finds that the expiry of an HGU does not automatically extinguish a pre-existing ulayat relationship, and that the State bears an obligation to verify indigenous claims before classifying ex-HGU land as State land. Legal protection should combine preventive measures (recognition, identification, and mapping of ulayat territory) with repressive mechanisms (administrative objection and litigation before the State Administrative Court).